ANALISIS KEPUASAN PENGGUNA UNIT LAYANAN PUBLIK (Riset Manajemen & Akuntansi, 2010)
The satisfaction of the user of public service unit in this research is influenced by the excellent service in public service organization which consists of several factors, which are: transparency, accountability, conditional, participative, right equivalence, and the balance between right and obligation. The problem in this research is whether the factors of transparency, accountability, conditional, participative, right equivalence, and the balance between right and obligation have influence toward the satisfaction of the user of public service unit. The purpose of this research is to investigate the influence of transparency, accountability, conditional, participative, right equivalence, and the balance between right and obligation factors. The research is done in Badan Pelayanan Terpadu Surakarta. The population is the society in Surakarta town who need the service of this agency. The sample taken is amounted of 272 people, by using purposive sampling. Data analysis used is double regression analysis. For testing the hypothesis, the researcher uses t-test and F-test. The conclusion is the variable of accountability, conditional, participative, right equivalence, and the balance between right and obligation independently has significant influence toward the satisfaction of the user of public service unit. Meanwhile, the transparency variable has no significant influence toward the satisfaction of the user of public service unit. The result of simultaneous test (F-test) answers the question that the variables of transparency, accountability, conditional, participative, right equivalence, and the balance between right and obligation simultaneously has significant influence toward the satisfaction of public service unit.